Application of Information Technology Tools in Addressing Specific Scheduling Challenges in Academic Timetabling - Dorota BORKOWSKA; Anna GLADYSZ (Communications of International Proceedings, 2025)
The process of planning teaching activities at a university is a complex decision-making process that requires consideration of numerous organisational, staffing and infrastructure constraints. Proper scheduling not only affects the efficient use of university resources, but also the comfort of lecturers and the quality of the teaching process. This article presents a proprietary approach to the automation of academic class scheduling, based on an analysis of practical experience in preparing teaching plans. Solutions enabling the mapping of non-standard planning cases are presented. The developed methodology contributes to increasing the efficiency of the planning process, reducing the number of planning errors and improving the quality of class organisation. The implementation of effective IT tools in the planning task can significantly improve the management of the teaching process, representing an important step towards its full automation and standardisation.
Keywords: Timetabling; scheduling; optimisation; FET